The Brexit Effect What Leaving the EU Means for British Politics - BALDINI, GIANFRANCO (Taylor & Francis, 2023)
This book examines the seismic impact of Brexit on the British political system, assessing its likely long-term effect in terms of a significantly changed political and constitutional landscape. Starting with the 2015 general elections and covering key developments up to 'Brexit day', it shows how Brexit 'transformed' British politics. The unprecedented turmoil - two snap elections, three Prime Ministers, the biggest ever defeat for the Government in Parliament, an impressive number of rebellions and reshuffles in Cabinet and repeated requests for a second independence referendum in Scotland - as a result of leaving the EU, calls into question what sort of political system the post-Brexit UK will become. Taking Lijphart's 'Westminster model' as its reference, the book assesses the impact of Brexit along three dimensions: elections and parties; executive-legislative relationships, and the relationship between central and devolved administrations. Based on a wealth of empirical material, including original interviews with key policy-makers and civil servants, it focuses on the 'big picture' and analytically maps the direction of travel for the UK political system. This book will be of key interest to scholars and students of Brexit, British Politics, constitutional, political, and contemporary history, elections and political parties, executive politics, and territorial politics as well as more broadly related practitioners and journalists.